Treatment plan optimization and robustness of 106Ru eye plaque brachytherapy using a novel software tool. Issue 1 (April 2017) - Heilemann, Gerd; Fetty, Lukas; Dulovits, Martin; Blaickner, Matthias; Nesvacil, Nicole; Georg, Dietmar; Dunavoelgyi, Roman
Abstract: Background and purpose: To analyze treatment plan robustness and plan optimization strategies of 106 Ru eye plaque brachytherapy using a novel software tool. Materials and methods: A treatment planning software was developed that allows to calculate dose–volume metrics. Plaque misplacements were simulated and evaluated with respect to the effect on tumor coverage and dose changes in critical structures. Two treatment plan optimization approaches were analyzed: (a) reducing plaque size and (b) shifting the plaque away from organs-at-risk (OAR). Results: Maximum tumor sizes were identified which can be covered by the prescribed dose for different robustness levels (0–2 mm). For an apex height of 5 mm a 1 mm uncertainty yielded changes in D 2% to the lens of up to ±13 Gy in anterior and ±20 Gy to the optic nerve in posterior tumors. By reducing the plaque size D mean and D 2% to lens, optic nerve and macula were decreased by >60% for most simulated cases. Similarly, by shifting the plaque away from the lens dose reductions of 15%/mm in anterior and even 30%/mm in central tumors were achieved. Conclusion: Critical structures in the treatment of uveal melanomas with 106 Ru plaques can benefit from the proposed, computational treatment plan optimization.